Effects of Music on Early Childhood Development in PAUD Benih Harapan and PAUD Siti Hajar Gorontalo City - Nancy Olii (Jurnal Nasional Ilmu Kesehatan, 2019)
ABSTRACT NANCY OLII S.SiT, MPH      Effects of Music on Early Childhood Development in PAUD Benih Harapan and PAUD Siti Hajar Gorontalo City                 Preschool-age children suffer from minor brain dysfunction, including impaired fine motor development, globally reported children to experience disorders in the form of anxiety, emotional, behavioral disorders, developmental disorders, both fine and gross motor development, hearing loss, lack of intelligence, delay talk, and one alternative to improve children's development is by playing music.               This study aims to analyze ‘The Effect of Music in Early Childhood Development in Harapan Harapan PAUD and Siti Hajar PAUD Dungingi District, Gorontalo City’.               This type of research includes the type of research Pre Experimental Design. With a pretest approach-posttest. The number of respondents was 30 children, who were observed before and after the act of listening to music. This research uses a purposive sampling technique. The independent variable is Music and the dependent variable is early childhood development.               The results of the study based on the analysis of the Paired t-Test with significance level α = 0.05 showed that there was a musical effect on early childhood development in ‘PAUD Benih Harapan’ and ‘PAUD Siti Hajar Gorontalo City’ with the acquisition of the Sig. (2-tailed) is 0,000 with the value α = 0.05 = (0,000 <0.05%).               Conclusion: There is an Effect of Music on early childhood development in ‘PAUD Benih Harapan’ and ‘PAUD Siti Hajar, Dungingi District, Gorontalo City’. Keywords : Music, Early childhood development